2020
DOI: 10.3390/cryst10090768
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Polarization Gratings Based on Nematic Liquid Crystal Mixtures Photoaligned with Azo Polymer-Coated Substrates

Abstract: Liquid crystal polarization gratings are of great interest for optical communications as elements performing beam steering, splitting, multiplexing or beam combining. Material birefringence, cell thickness or a period of the liquid crystal director pattern influence, among other features, spectroscopic and electro-optical characteristics of fabricated devices, determining thus their functionality and applicability. Here, we report on liquid crystal polarization gratings that allow for complete maximization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Additionally, LC-based diffraction gratings with no polymer added to the material have been demonstrated. In those cases, the gratings were either created by irradiation of photosensitive alignment layers [32][33][34][35][36][37][38] or by introducing the LC into LC cells with periodic electrodes [39]. Moreover, the diffraction efficiencies of the presented LC-based diffraction gratings were dependent on polarization of incident light and the value of applied voltage in cases of the ones with periodic electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LC-based diffraction gratings with no polymer added to the material have been demonstrated. In those cases, the gratings were either created by irradiation of photosensitive alignment layers [32][33][34][35][36][37][38] or by introducing the LC into LC cells with periodic electrodes [39]. Moreover, the diffraction efficiencies of the presented LC-based diffraction gratings were dependent on polarization of incident light and the value of applied voltage in cases of the ones with periodic electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it is difficult to realize grating periods smaller than the thickness of the layer. Gratings of 10 μm, 21 5 μm 22 and 3.4 μm 4 have been reported. Kun et al reported optical axis gratings with a period down to 2.2 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Tunability is one of the important properties of diffraction gratings. Various tuning methods have been proposed; diffractive properties can be modulated by an applied electrical voltage [ 25 , 26 , 27 , 28 ], magnetic field [ 29 , 30 , 31 ], pressure, temperature, or by another electromagnetic wave [ 32 , 33 , 34 , 35 , 36 , 37 ]. Liquid crystals (LCs) are very suitable for the construction of tuneable optical diffraction gratings [ 38 , 39 ] since they possess a unique combination of mechanical softness and strong optical anisotropy that provides relatively easy control of LC molecules’ orientation.…”
Section: Introductionmentioning
confidence: 99%